1979
DOI: 10.1007/bf00918902
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of problem behavior in deaf children

Abstract: The Behavior Problem Checklist was completed by the teachers of 192 deaf students who attended a special day school for the deaf. Three separate factor analyses were performed. Four factors that correspond to the dimensions found in earlier research and previously labeled conduct disorder, personality problems, immaturity-inadequacy, and socialized delinquency were found. An additional factor labeled passive inferiority was also extracted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
16
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 7 publications
3
16
0
Order By: Relevance
“…This scoring procedure was established by Quay and Peterson (1975) to generate comparative data from studies of various types of children. Consequently, using this procedure allows for a direct comparison of the prevalence of behavior problems in deaf children from the Hirshoren and Schnittjer (1979) study to that of other groups of children from prior studies.…”
Section: Analysis Of the Datamentioning
confidence: 99%
See 3 more Smart Citations
“…This scoring procedure was established by Quay and Peterson (1975) to generate comparative data from studies of various types of children. Consequently, using this procedure allows for a direct comparison of the prevalence of behavior problems in deaf children from the Hirshoren and Schnittjer (1979) study to that of other groups of children from prior studies.…”
Section: Analysis Of the Datamentioning
confidence: 99%
“…There currently exists a significant body of research that attests to the reliability, validity, and usefulness of the Behavior Problem Checklist (BPC) (Quay & Peterson, 1975), a 55-item factorially-derived rating scale, in a wide variety of settings with various types of raters for different groups of handicapped and delinquent children (Quay & Peterson, 1975). The appropriateness of the BPC for use with deaf children has been investigated by Reivich and Rothrock (1972) and by Hirshoren and Schnittjer (1979). Both studies found that, with minor variations, the factorial structure of the BPC found by Quay and Peterson (1975) in juveniles with intact hearing appears to hold with hearing-impaired children.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of these studies suggest that while the hearing impaired share the emotional/behavioral problems evident in other populations, such as difficulties in psychological adjustment (Brunschwig, 1972;Myklebust, 1960;Naiman, 1965;Schlesinger, 1978;Vernon, 1969) or poorly developed self-concepts (Best, 1973;Mehan, 1978;Schlesinger, 1978), they may also exhibit emotional problems which are specific to the hearing impaired population (Best, 1973;Hirshoren & Schnittjer, 1979;Reivich & Rothrock, 1972).…”
mentioning
confidence: 95%